2021
DOI: 10.3390/app11094091
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Feature-Based Methodology to Perform Cervical Cancer Classification

Abstract: Prevention of cervical cancer could be performed using Pap smear image analysis. This test screens pre-neoplastic changes in the cervical epithelial cells; accurate screening can reduce deaths caused by the disease. Pap smear test analysis is exhaustive and repetitive work performed visually by a cytopathologist. This article proposes a workload-reducing algorithm for cervical cancer detection based on analysis of cell nuclei features within Pap smear images. We investigate eight traditional machine learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 58 publications
(68 reference statements)
0
6
0
1
Order By: Relevance
“…A workload-reducing algorithm for analysis of cell nuclei features from Pap smear images. An investigation has been done with the involvement of eight traditional machine learning methods to perform a hierarchical classification [41] Morphological and other features are also included in the study. The study found that hierarchical classification provided better findings than those without it.…”
Section: Detection Methods Based On Cells/pap Smear Imagesmentioning
confidence: 99%
“…A workload-reducing algorithm for analysis of cell nuclei features from Pap smear images. An investigation has been done with the involvement of eight traditional machine learning methods to perform a hierarchical classification [41] Morphological and other features are also included in the study. The study found that hierarchical classification provided better findings than those without it.…”
Section: Detection Methods Based On Cells/pap Smear Imagesmentioning
confidence: 99%
“…It is a powerful supervised machine learning algorithm that is capable of performing both classification and regression tasks with high accuracy [18]- [20]. Various studies in the medical area have used RF algorithms to, for example, diagnose diabetes mellitus [21], [22], identify cervical cancer [23]- [25], or predict the risk of severity for COVID-19 patients at hospital admission [26].…”
Section: Model Trainingmentioning
confidence: 99%
“…They evaluated the performance with the Support Vector Machine (SVM), k-Nearest Neighbors (k-NN), and Random Forest (RF) algorithms, and 31 sets of characteristics. Isidoro et al [6] used a SVM to classify images of cervical cells obtained in Pap smear through the extraction of nongeometric characteristics, while Diniz et al [14] used a hierarchical methodology and geometric characteristics.…”
Section: Related Workmentioning
confidence: 99%